2009
DOI: 10.1061/(asce)0733-9364(2009)135:6(466)
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Use of Negotiators’ Tactics in Construction Dispute Negotiation

Abstract: In the course of negotiation, negotiators' tactics should be responsive to the situational factors. This is commonly described as the contingent use of negotiators' tactics. This study examines this concept in construction dispute negotiation (CDN) and has three stages of work. Stage 1 develops taxonomies of the three construction dispute negotiation dimensions: dispute sources, negotiators' tactics and negotiation outcomes by exploratory factor analysis (EFA). A structural equation modeling (SEM) is also used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Behaviorists have attributed this happening to the influence of negotiators' personal qualities -personality (O'Connor, Gladstone 2015). Cheung et al (2009) further found that a negotiator's personality is intrinsically linked to his choice of tactic because personality influences the way a negotiator interprets a dispute. For example, a cooperative negotiator may view a challenge by his counterpart as an attempt to explore better options, but a competitive negotiator may view the same challenge as a threat.…”
Section: Introductionmentioning
confidence: 99%
“…Behaviorists have attributed this happening to the influence of negotiators' personal qualities -personality (O'Connor, Gladstone 2015). Cheung et al (2009) further found that a negotiator's personality is intrinsically linked to his choice of tactic because personality influences the way a negotiator interprets a dispute. For example, a cooperative negotiator may view a challenge by his counterpart as an attempt to explore better options, but a competitive negotiator may view the same challenge as a threat.…”
Section: Introductionmentioning
confidence: 99%
“…Sai On Cheung, Pui Ting Chow, and Tak Wing Yiu () identified tactics in the literature and ranked them according to usefulness. They found, for example, that negotiators use procedure ‐ focused tactics (Rahim ) such as making counter‐offers and offering trade‐offs across issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Progress seeking tactics seek to break stalemates by, for example, focusing on time pressures by emphasizing deadlines (De Dreu and Van Kleef ). The last category in Cheung, Chow, and Yu's () taxonomy, option generating , comprises tactics that help the parties identify mutually beneficial options (Walton and McKersie ). Mara Olekalns, Philip Smith, and Therese Walsh () proposed a taxonomy of six groups of tactics they categorized broadly as either cuing or responding, including restructuring , priority information , making concessions , positional information , and rejection .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, organizations can adopt principled negotiation for all types of disagreements to maintain a harmonious relationship throughout the process and avoid adverse impacts on the project (Cheung et al 2009). It also decreases monitoring cost and increases the possibility of achieving mutually beneficial agreements (Khalfan et al 2007).…”
Section: Mediation Effect Of Principled Negotiationmentioning
confidence: 99%